Bronchiectasis with Multiple Bullae Post-Extraction Corpus Alineum Comorbid with Pulmonary Tuberculosis - Dewi Wahyu Fitrina; Yulia Helexandra (HM Publisher, 2022)
Background. Bronchiectasis is a chronic inflammatory airway disease characterized by chronic bronchial dilatation. The cause of bronchiectasis is still ideopathic but most of the bronchiectasis are caused by tuberculosis infection and will interfere with the patient's quality of life. In addition, bronchiectasis can be caused by aspiration of foreign bodies. Case presentation. A 42-year-old male patient was treated at Dr, M Djamil Padang Hospital with complaints of coughing up blood, in addition the patient complained of coughing up yellowish phlegm, shortness of breath and fever. The patient had a history of foreign body aspiration 6 months ago. The patient had a chest X-ray and a chest CT scan and a picture of bronchiectasis and mulltiple bullae was found. The patient also had pulmonary tuberculosis infection where the X-pert gene examination in the patient found that MTB was not detected. Conclusion. The patient had multiple bullae, which were complications of emphysema, and the patient had or had compensatory emphysema, where the abnormality was hyperinflation of certain parts of the lung due to atelectasis. The condition of bronchiectasis and multiple bullae makes the patient susceptible to infection, which in this case was found to have pulmonary tuberculosis infection. Management of bronchiectasis includes identification of acute exacerbations and the use of antibiotics, controlling microbial growth, treatment of the underlying condition, and reducing the excessive inflammatory response.